AKTIVITAS PENGHAMBATAN Î±-GLUCOSIDASE PADA MINUMAN JELI KULIT MELINJO KUNING [ACTIVITY OF Î±-GLUCOSIDASE INHIBITION ON JELLY DRINK OF YELLOW MELINJO PEELS (Gnetum gnemon L.)] - Mastuti, Titri Siratantri; Lausane, Aurelia Clara; Siregar, Tagor M. (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2018)
Melinjo peel has a high content of polyphenol compounds, is expected to inhibit the activity of the enzyme Î±-glucosidase. The activity of Î±-glucosidase is related to the absorption of glucose and blood sugar. The content of polyphenols in the melinjo peel can be utilized more optimally by making the juice of melinjo fruit peel and processed as a jelly drink. Making jelly drinks requires hydrocolloids as a gelling material. The objective of the research are to determine the type of melinjo peel juice that has the best Î±-glucosidase inhibition activity and determine the ratio of melinjo peel juice  and the best percentage of hydrocoloid in the making of jelly drinks. The first stage of research is to determine the type of melinjo peel  red, yellow, and green that will be selected into the best melinjo skin juice that has inhibitory activity Î±glucosidase and also has the best antioxidant activity. The second stage of research is making the best jelly drinks with treatment ratio between water and melinjo peel juice and percentage of the amount of hydrocoloid used. IC 50 of Î±-glucosidase inhibition activity yellow melinjo peels juice is 22,393 ppm as the highest activity. Based on organoleptic, color, texture, pH, total soluble solid, and syneresis tests that were done to all samples of jelly drink, the selected jelly drink is the one with 50:50 ratio of yellow melinjo peels juice to water and concentration of hydrocoloid of 0.20%. The jelly drink has IC 50  Î±-glucosidase inhibition of 30,974 ppm, antioxidant activity of 12.4054 mg VCE/100mL, phenolic total of 0.4037 mg GAE/g, flavonoid total of 0.0173 mg QE/g. ABSTRAKKulit melinjo memiliki kandungan senyawa polifenol yang tinggi, diharapkan dapat menghambat aktivitas enzim Î±-glukosidase. Aktivitas Î±-glukosidase berhubungan dengan penyerapan glukosa dan kadar gula di dalam darah. Kandungan polifenol pada kulit melinjo dapat dimanfaatkan secara lebih optimal dengan cara mengambil sari kulit buah melinjo dan diolah sebagai minuman jeli. Pembuatan minuman jeli memerlukan hidrokoloid sebagai bahan pembentuk jel. Penelitian ini bertujuan untuk menentukan jenis sari kulit melinjo yang memiliki aktivitas penghambatan Î±-glukosidase terbaik serta menentukan rasio sari kulit melinjo dan persentase hidrokoloid terbaik dalam pembuatan minuman jeli. Tahap pertama penelitian adalah menentukan jenis kulit melinjo merah, kuning, dan hijau yang akan dipilih menjadi sari kulit melinjo yang memiliki aktivitas penghambatan Î±-glukosidase dan juga memiliki aktivitas antioksidan terbaik. Tahap kedua penelitian adalah pembuatan minuman jeli dengan perlakuan rasio antara sari kulit melinjo dan air serta konsentrasi  hirokoloid  yang dipakai. Aktivitas penghambatan Î±-glukosidase tertinggi diperoleh dari sari kulit melinjo kuning d engan nilai IC50 sebesar 22.393 ppm. Berdasarkan uji organoleptik, warna, tekstur, pH, total padatan terlarut, dan sineresis, minuman jeli terpilih dengan rasio sari kulit melinjo kuning:air 50:50 dan konsentrasi hidrokoloid  0,20%. Minuman jeli sari kulit melinjo kuning memiliki nilai IC50 penghambatan  Î±-glukosidase 30974 ppm, aktivitas antioksidan 12,4054 mg VCE/100mL, total fenolik  0,4037 mg GAE/g, total flavonoid 0,0173 mg QE/g.Kata kunci : aktivitas antioksidan, Î±-glukosidase, hidrokoloid, kulit melinjo, minuman jeli